Efficacy of Inactivated Bivalent SARS-CoV-2 Vaccines Targeting Ancestral Strain (ERAGEM), Delta, and Omicron Variants - Kaplan, Busra; Pavel, Shaikh Terkis Islam; Uygut, Muhammet Ali; Tunc, Merve; Eroksuz, Yesari; Celik, Ilhami; Yetiskin, Hazel (Mdpi, 2025)
Background/Objectives: The rapid evolution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to the emergence of variants with enhanced transmissibility and immune evasion, challenging existing vaccines. This study aimed to evaluate the immunogenicity and protective efficacy of inactivated bivalent vaccine formulations incorporating the ancestral SARS-CoV-2 strain (ERAGEM) with either Delta or Omicron (BA.5) variants. Methods: Bivalent vaccine formulations were prepared using beta-propiolactone-inactivated SARS-CoV-2 antigens and administered to K18-hACE2 transgenic mice. Following prime and booster immunizations, neutralizing antibody titers and viral loads were assessed through ELISA, microneutralization assays, and quantitative PCR. Mice were challenged with the respective variants, and the survival rates, temperature, and body weight changes were monitored for 21 days. Results: Both vaccine formulations elicited significant increases in neutralizing antibody titers post-booster immunization. The ERAGEM + Delta group demonstrated geometric mean titers (GMTs) of 6938.1 and 4935.0 for the ancestral and Delta variants, respectively, while the ERAGEM + Omicron (BA.5) group achieved GMTs of 16,280.7 and 24,215.9 for the ancestral and Omicron (BA.5) variants. Complete survival (100%) was observed in all the vaccinated groups post-challenge, with no detectable viral titers in the lungs and substantial reductions in the nasal turbinate viral loads compared to the unvaccinated controls. Conclusions: The bivalent inactivated vaccines demonstrated strong immunogenicity and complete protection against severe disease in preclinical models. These findings indicate the potential of bivalent vaccine strategies in addressing antigenic diversity and preparing for future pandemics caused by rapidly evolving pathogens.
Keywords: SARS-CoV-2; bivalent vaccine; inactivated vaccine; immune response; pandemic preparedness